SOSIALISASI PEMILIH PEMULA GUNA MENINGKATKAN PARTISIPASI POLITIK PADA PILKADA 2024 DI DESA ADIREJO KECAMATAN PEKALONGAN - Mirnawati, Mirnawati; Intan Destrilia; Daud Husni; Yuyun Fitriani (Yayasan Nusantara Hasana Berdikari, 2025)
The purpose of this community service program is to enhance political participation among first-time voters in the 2024 local elections. The location for this service isi in Adirejo village, Pekalongan District, East Lampung Regency. To achieve the desired goals of this service, several methods have been employed, including core and supplementary programs. These include outreach efforts to the youth of Adirejo village, Pekalongan District, related to socialization for first-time voters, aimed at increasing political participation in the 2024 local elections in Adirejo village. The hope of implementing this service activity is that teenagers, especially those in the age category of beginner voters in Adirejo Village, will have a better understanding of how to use their voting rights to participate in the 2024 regional election activities.